Synthesis, Characterization and Antibacterial Study of New 4-Thiazolidinone and Tetrazole Compounds Derived from Thiosemicarbazone and Hydrazones - Israa A. Mosa (Journal of Global Pharma Technology, 2019)
A new 4-thiazolidinone, substitutedbenzylidene-thiazolidinone and tetrazole were synthesized from thiosemicarbazone and hydrazone. The thiosemicarbazone was prepared by the reaction of thiosemicarbazide with aldehyde derivative from L-ascorbic acid in absolute ethanol using glacial acetic acid as a catalyst. 1, 3-thiazolidin-4-ones were synthesized from the condensation of thiosemicarbazones with chloroacetic acid in presence of anhydrous sodium acetate. A 1, 3- thiazolidine-4-one was reaction with several 4-substitutedaldehydes to produce new derivatives with a double bond at the position-5 of the 4-thiazolidinone ring. While the tetrazole compounds were synthesized by 1, 3-cycloaddition reaction of sodium azide and hydrazone compounds in dimethylformamide. The hydrazone compounds were prepared by the reaction of phenylhydrazine or substituted phenylhydrazine with aldehyde derivative from L-ascorbic acid in absolute ethanol using glacial acetic acid as a catalyst. The structures of newly synthesized compounds were established on the basis of spectroscopy data.Keywords: L-Ascorbic acid, 4-Thiazolidinone, Alken, Thiosemicarbazone, Tetrazole, Hydrazone.